10
Quiz 7 The way I expected it.

Quiz 7

  • Upload
    idana

  • View
    21

  • Download
    1

Embed Size (px)

DESCRIPTION

Quiz 7. The way I expected it. How to do it!. 1. Let P(n) be the statement that 1 2 + 2 2 + ... + n 2 = n(n + 1)(2n + 1)/6 for the positive integer n . Be sure to use the formal proof that includes the Basis Step. State what you are trying to prove!. - PowerPoint PPT Presentation

Citation preview

Page 1: Quiz 7

Quiz 7

The way I expected it.

Page 2: Quiz 7

How to do it!

1. Let P(n) be the statement that 12 + 22 + ... + n2 = n(n + 1)(2n + 1)/6 for the positive integer n.

Be sure to use the formal proof that includes the Basis Step

Page 3: Quiz 7

State what you are trying to prove!

Prove 12 + 22 + ... + n2 = n(n + 1)(2n + 1)/6 for the positive integer n.

Positive integer n means 1, 2, 3, …

Page 4: Quiz 7

Basis Step

Let P(n) be the statement that 12 + 22 + ... + n2 = n(n + 1)(2n + 1)/6 for the positive integer n.

(a) Basis Step: plugging in n = 1 we have that P(1) is the statement: (1)2 = (1)((1) + 1)(2(1) + 1)/6

Expanding both sides we have:1 = 1 * 2 * 3/6 = 1

Both sides of P(1) shown in part (a) equal 1.Here we are just plugging in the smallest positive integer and showing that both sides are equivalent.

Page 5: Quiz 7

Inductive Hypotheses

(b) Inductive Hypotheses: The inductive hypothesis is the statement that

12 + 22 + ... + k2 = k(k + 1)(2k + 1)/6 Here we substitute k for n and restate what we are trying to

prove.

Page 6: Quiz 7

Inductive step

(c) For the inductive step, we want to show for each k ≥ 1 that P(k) implies P(k + 1). In other words, we want to show that by assuming the

inductive hypothesis we can prove (12 + 22 + ... + k2) + (k + 1)2

= (k + 1) ((k + 1) + 1)(2(k + 1) + 1)/6

We take the last k term on the left side , (k)2, add another similar term with the k value replaced by k + 1, and replace all k terms on the right-hand side by k + 1 terms.

Page 7: Quiz 7

Substitution Proof(d) Replacing the quantity in brackets on the left-hand side of part(c) by what it equals by virtue of the inductive hypothesis k(k + 1)(2k + 1)/6 + (k + 1)2 = (k + 1) ((k + 1) + 1)(2(k + 1) + 1)/6, we have

k(k + 1)(2k + 1)/6 + (k + 1)2 = (k + 1) ((k + 1) + 1)(2(k + 1) + 1)/6 k(k + 1)(2k + 1)/6 +6 (k + 1)2/6 = (k + 1) ((k + 1) + 1)(2(k + 1) + 1)/6 (k(2k + 1) + 6 (k + 1))/6 = (k + 2)(2k + 3)/6 {divide both sides by (k + 1)} (k(2k + 1) + 6 (k + 1)) = (k + 2)(2k + 3) {multiply both sides by 6}2k2 + k + 6k + 6 = (k + 2)(2k + 3) {expand both sides}2k2 + 7k + 6 = 2k2 + 7k + 6 {divide both sides by 2k2 + 7k + 6 }1 = 1 {both sides equal}

we have shown that both sides are equal as we desired.

Page 8: Quiz 7

N Factorial

2. Convert the following recursive function into a recursive algorithm (using the pseudo format specified in appendix A3):

f(0) = 1f(n + 1) = (n + 1) * f(n)

procedure factorial(n: nonnegative integer)if n = 0 then return 1else return n ∙ factorial(n − 1){output is n!}

Page 9: Quiz 7

A Recursive Algorithm for Computing nk=0 ak

3. Bonus: a. Give a recursive algorithm (in the

pseudo format specified in appendix A3) for computing:

nk=0 ak = a0 + a1 + a2 + … + an

procedure series (a: list of nonzero real numbers, n: nonnegative integer)

if n = 0 then return a0

else return an + series (a, n − 1){output is a0 + a1 + a2 + … + an}

Page 10: Quiz 7

Bonus

b. Using 3. above, show the value of ak generated at each step given a0= 1 and n= 4.

(missing information a1 = 2, a2 = 3, a3 = 4, a4 = 5)

Green is the values that missing info would have provided!Red is what you could have provided without missing info!

n 0 1 2 3 4

an a0 a0 + a1 a0 +a1+ a2 a0 + a1 + a2 + a3 a0 + a1 + a2 + a3 + a4

1 3 6 10 15